Factors contribute to effective layout among kiosk in Plaza Angsana, Johor Bahru/ Nor Fazwani Najwa Mohd Nor - Mohd Nor, Nor Fazwani Najwa (Faculty of Business and Management, 2013)
As requirement to complete the internship program, I have completed this research on “Effective Kiosk Layout”. In this research three (3) independent variables that affect effective layout among kiosk have been identified which are customer movement, customer capacity and mall’s environment. Research has been done at Plaza Angsana, Johor Bahru on kiosk’s tenants. The researcher had taken 58 tenants as respondents which they come from all kiosks’ tenant. That means the researcher had used census technique in this research. Objectives of the study are to investigate the relationship of movement, capacity and environment towards an effective layout and also to investigate the most factors that significantly contribute towards effective layout. Finding on this research through the comparison of Adjusted R-square in Model Summary (table 4.6.1) have shown that the result is 34.4% from the three (3) independent variables are able to explain the relationship effective kiosk layout.